2015
DOI: 10.1177/2325967115s00092
|View full text |Cite
|
Sign up to set email alerts
|

United States Trends in Medial Ulnar Collateral Ligament Reconstruction: A retrospective Review of a Large Private-Payer Database from 2007 to 2011

Abstract: Objectives:Purpose: Overuse injuries to the elbow in the throwing athlete are common. Ulnar collateral ligament reconstruction (UCLR), commonly known as Tommy John surgery, is performed on both recreational and high-level athletes. There is no current literature regarding the incidence and demographic distribution of this surgical procedure in relation to age, location within the Unites States (U.S.), and gender. The purpose of this study is to determine the current demographic distribution of UCLR within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
157
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(162 citation statements)
references
References 0 publications
4
157
1
Order By: Relevance
“…3,6,8 The goals of this study were to report the patent demographics, clinical outcomes, return-to-sport rate, and complications for all UCLRs performed at a single institution from January 2004 to December 2014. The most common graft choice in this study was an ipsilateral palmaris longus autograft, used in 59.3% of patients, followed by a hamstring autograft, used in 25.4% of patients (Table 4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3,6,8 The goals of this study were to report the patent demographics, clinical outcomes, return-to-sport rate, and complications for all UCLRs performed at a single institution from January 2004 to December 2014. The most common graft choice in this study was an ipsilateral palmaris longus autograft, used in 59.3% of patients, followed by a hamstring autograft, used in 25.4% of patients (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…There has been a trend in the literature toward younger patients undergoing UCLR, with a recent increase in the percentage of high school athletes compared with other levels. 3,8 A recent study on national trends in UCLR between 2007 and 2011 using the Pearl Diver database showed that UCLR was most commonly performed in 15-to 19-year-old patients; 57% of all patients undergoing UCLR fell into this age group. 8 Although injury prevention programs have been instituted over the past decade to protect adolescent athletes from injury, these programs have yet to yield a significant decline in injury rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rising incidence of ulnar collateral ligament reconstructions performed in young overhead throwing athletes from 1995 to 2015, based on publicly available data of the American Sports Medicine Institute and Erickson (2015) 4. UCL, ulnar collateral ligament.…”
Section: Considerationmentioning
confidence: 99%
“…Ulnar collateral ligament (UCL) tears represent one of the most common elbow injuries in baseball players. Evidence suggests that the rate of UCL injuries in baseball players has been rising dramatically in recent years 2. Baseball pitchers put very high amounts of stress through their elbow when pitching.…”
Section: Introductionmentioning
confidence: 99%